Goya and tinea favosa - Andrelou Fralete Ayres Vallarelli (Sociedade Brasileira de Dermatologia, 2014)
A case of a tinea favosa involving the scalp of a child represented in the painting "Boys climbing a tree" (Muchachos trepando a un árbol), by Francisco Goya y Lucientes, with pictorial representation of favic scutula and consequent alopecia.